(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study analyzed the social and economic effect of commercial flight delay in Nnamdi Azikiwe International airport [NAIA], this is to help to monitor, identify and improve on the challenges being faced by airliners operation in NAIA owing to flight delay. Data were obtained from both primary (questionnaires and interview) and secondary sources (FAAN and airline offices at the NAIA), and were analyzed using descriptive statistics with a sample size of 400 respondents selected purposively. Findings of the study revealed that majority of the respondents (83.5%) travel more than one time in a year for business, leisure and tourism, education, visit to family, and official purpose, and that 89% of these respondents have experienced flight delay with the perceived causes including but not limited to technical issues (20.5%), weather (15.8%) and traffic among others. The study also revealed that about 65.4% of the respondents have experienced flight delay about 5times within the study period. he study finds that most flights are delayed for 1-5hours. Flight delay has negative social and economic effects on travellers. The study recommended that timely weather information is needed to limit flight delay associated with weather while alternative airplane should be made available when technical issues arises. Also, airline operators should pay attention to the nature of their flight delays so as to structure mitigation strategy that help them tackle it. Though there are no remedies to some social losses, airline operators should endeavour to compensate travellers affected by delay